Perkembangan Bisnis Pariwisata Di Kota Parapat Ditinjau Dari Perspektif Pembangunan Danau Toba Sebagai “Monaco Of Asia” - Nalom Siagian; Steven Jordan Siallagan (LPPM Universitas HKBP Nommensen, 2022)
This study aims to determine the development of the tourism business in the area of ​​Lake Toba, Parapat City, Girsang Sipanganbolon District in terms of the perspective of developing Lake Toba as an international class